Floristic groups, and changes in diversity and structure of trees, in tropical montane forests in the southern andes of Ecuador - Jadán, Oswaldo (2021)
Composition, diversity, and structure of trees in tropical montane forests are responsive to ecological gradients and local succession. Those parameters are a result of ecological interactions between vegetation, environment, and location. This study identified floristic groups on mainly secondary forests and evaluated how the composition, diversity, and structure of trees correlate with climate, soil, and age since abandonment. We included in our models a measurement of spatial correlation, to explore the role of dispersion. For this purpose, we measured diameter and height of all trees with DBH ≥ 10 cm, in twenty-eight 500 m2 plots, in an elevation range between 2900 and 3500 m. We found 14 indicator species in three floristic groups. Group composition was explained by age since abandonment, which showed strong succession effects. Mean monthly precipitation and Manganese, but not spatial correlation, explained plant composition in these montane forests, suggesting a minor role of dispersion. Species richness and structure of the arboreal vegetation were influenced by interactions between age, precipitation, and soil nutrients concentration. We concluded that in fragmented landscapes, within the rugged region of southern Ecuador, it is possible to find different floristic groups that encompass high variation in their composition.